Evaluation of Long-Term Lymphedema Rate in Patients With Subclinical Lymphedema Diagnosed in the Preoperative Period via Bioimpedance - Zeynep Erdoğan İyigün; Tolga Ozmen; Serkan İlgün; Cansu Nakipoğlu; Enver Özkurt; Filiz Çelebi; Çağlar Ünal; Alper Öztürk; Gül Alço; Çetin Ordu; Gürsel Soybir (European Journal of Breast Health)
Objective: The aim of this study was to evaluate the relationship between subclinical lymphedema identified prior to surgical intervention and clinical lymphedema observed in the late period, the incidence of lymphedema in our cohort, and the associated risk factors. Materials and Methods: This prospective study was conducted with early-stage breast cancer patients who had been enrolled in a previous study. For diagnosing lymphedema, physical examination, L-Dex® score, and circumferential measurement was used. The L-Dex® score was used as a screening test for preoperative, subclinical lymphedema since there were no clinical findings. Patients with subclinical lymphedema were provided with education and followed up more frequently with regular monitoring. Results: The mean age of the 217 participants was 56.7±12.7 years (range 29–90), and the mean body mass index was 27.7±3.3 kg/m2 (range 19.3–36.9). Among the 217 patients, lymphedema was detected in 31 (14.7%) at a median follow-up period of 89 months (range 73–108 months). Multivariable analysis of factors associated with late-stage lymphedema revealed positive lymph node count and capsular invasion as significant factors (p = 0.001 for both). Forty (18.4%) had preoperative subclinical lymphedema. At the end of the follow-up period, lymphedema persisted in 11 patients (27.5%) and resolved in 29 patients (72.5%). In multivariable analysis, the positive lymph node count was identified as an independent variable in these patients. Conclusion: Identifying high-risk patients, regular monitoring, and early intervention can significantly reduce the risk of clinical lymphedema through timely treatment.